Pengaruh Penambahan Serat Kepompong Ulat Sutra (Bombyx mori L.) terhadap Kekuatan Fleksural Resin Komposit Flowable - Sumantri, Tiaradenta Dyah Ayu; , Drg. Dendy Murdiyanto, MDSc (2017)
Flowable composite resin had low viscosity and easy to apply because it was containing high TEGDMA matrix, but it resulted in low mechanical strength, so there was need to add silkworm cocoon fiber to increase composite resin mechanical strength. Silkworm (Bombyx mori L.) cocoon fiber was one of the natural fiber from animal source. Silkworm cocoon fiber containing fibroin that had role as reinforcement to improve composite resin mechanical strength. The objective of this research is to determine the effect of adding fiber silkworm cocoons to flexural strength of flowable composite resins and to determine the effect of adding fiber silkworm cocoons to the increase in the flexural strength of flowable composite resins. This study used 32 flowable composite resin specimens block-shape with the block size was 25x2x2 mm. The specimen divided into control group and treatment group. Each group consist of 16 specimens. Speciment in the treatment group was added with silkworm cocoon fiber and the control group was not. Independent t-test result showed that there is significant difference (p<0,05) between control group and treatment group. Conclusion of this study was silkworm cocoon fiber addition influential to the flexural strength flowable composite resin. Silkworm cocoon fiber addition improved to the flexural strength flowable composite resin.